Identifikasi Keanekaragaman dan Dominansi Gulma Pada Lahan Pertanaman Mangga Gedong Gincu di Desa Lohbener Indramayu - Dwimartina, Fina; Asad, Faisal Al (Universitas Wiralodra, 2025)
Mango plants can grow optimally if planted in a suitable environment, but will be hampered if there are factors inhibiting their growth. Weeds are plants that can limit or inhibit the growth of plants cultivated on a land (1). This is because weeds become competitors for the main plants in obtaining nutrients, water, light and growing space (2). Weeds can also host major plant pathogens and pests (3) and can produce allelochemical compounds, namely chemical compounds that can suppress the growth of cultivated plants through an allelopathic process (4). It is important to study weed diversity to determine the composition and structure of weeds in mango plantations and to determine appropriate control. Weed diversity is influenced, among other things, by environmental conditions (5). The aim of this research is to determine the diversity and dominance of weeds in mango plantations. This research uses a qualitative method by identifying sample weeds, as well as a quantitative method by analyzing weed vegetation. Sampling was carried out using the Quadratic method using plots measuring 0.5×0.5 m2 randomly by throwing the plots into the mango cultivation land 10 times so that there were 10 sample plots. The results of the research showed that in the Gedong Gincu mango plantations in Lohbener Indramayu Village, 2 groups of weeds were found, namely grass weeds consisting of 1 species, and broadleaf weeds consisting of 2 species. The dominant weeds on the land are Imperata cylindrica (SDR value 56.94%), and Ruellia tuberosa (SDR value 19.19%).